Lean Resilience Readiness: Systematic Literature Review & A Case Study of Burmese Manufacturing Firms - Tin, Soe (2022)
Abstract The rapid changes in the supply chain sector force companies to improve the resilience level of a business in terms of operational efficiency and availability of raw materials. Improving the resilience in lean manufacturing is controversial as they have opposite natures. Generally, people think that a lean strategy can reduce costs and minimise the waste that reduces a business’s resilience. However, the idea of improving resilience with the lean concept is relatively new and very few studies were conducted. Therefore, the primary contribution of this work is a comprehensive evaluation of the current literature on lean and resilience, with the goals of supplying direction on the topic, revealing gaps and inconsistencies in the literature, and identifying new research directions. The study uses a concept map to identify and organise six primary lines of inquiry, all of which have contributed to our understanding of the literature on the subject of organisations and industries. The study aims to reveal the relationship between lean and resilience and how the level of leanness can help improve resilience. Moreover, the solution for balancing leanness and resilience will be described. The important aspects are suggested in the research question, and the balancing issue will be described individually in a session as it is the most important session. Finally, the interview session will provide the differences between the real world and academics.